Mitochondrial C3a Receptor Activation in Oxidatively Stressed Epithelial Cells Reduces Mitochondrial Respiration and Metabolism - Ishii, Masaaki; Beeson, Gyda; Beeson, Craig; Rohrer, Bärbel (Frontiers in Immunology, 2021)
Complement component 3 fragment C3a is an anaphylatoxin involved in promoting cellular responses important in immune response and host defense. Its receptor (C3a receptor, C3aR) is distributed on the plasma membrane; however, lysosomal localization in immune cells has been reported. Oxidative stress increases intracellular reactive oxygen species (ROS), and ROS activate complement signaling in immune cells and metabolic reprogramming. Here we tested oxidative stress and intracellular complement in mitochondrial dysfunction in RPE cells using high resolution live-cell imaging, and metabolism analysis in isolated mitochondria using Seahorse technology. While C3aR levels were unaffected by oxidative stress, its cell membrane levels decreased and mitochondrial (mt) localization increased. Trafficking was dependent on endocytosis, utilizing endosomal-to-mitochondrial cargo transfer. H2O2-treatment also increased C3a-mtC3aR co-localization dose-dependently. In isolated mitochondria from H2O2-treated cells C3a increased mitochondrial Ca2+ uptake, that could be inhibited by C3aR antagonism (SB290157), mitochondrial Ca2+ uniporter blocker (Ru360), and Gi-protein inhibition (pertussis toxin, PTX); and inhibited mitochondrial repiration in an SB290157- and PTX-dependent manner. Specifically, mtC3aR activation inhibited state III ADP-driven respiration and maximal respiratory capacity. Mitochondria from control cells did not respond to C3a. Furthermore, transmitochondrial cybrid ARPE-19 cells harboring J haplogroup mitochondria that confer risk for age-related macular degeneration, showed high levels of mtC3aR and reduced ATP production upon C3a stimulation. Our findings suggest that oxidative stress increases mtC3aR, leading to altered mitochondrial calcium uptake and ATP production. These studies will have important implication in our understanding on the balance of extra- and intracellular complement signaling in controlling cellular health and dysfunction.